UPAYA MENINGKATKAN KESEHATAN MASYARAKAT GANTAR MELALUI KEGIATAN SENAM PAGI DI PUSKESMAS GANTAR - Fara Dhiyah Hasni; Aidi Agung Sani; Moch. Irfan Malindo; Irvan Iswandi; Dede Indra Setiabudi (Pusat Riset dan Inovasi Nasional, 2022)
Gymnastics is a body exercise that is chosen and created deliberately and planned, systematically arranged with the aim of forming and developing a harmonious whole. Gymnastics is one of the most popular sports in society. The results of the morning gymnastics activities in the public health field carried out by KKN Kelompok Garuda students which were carried out on Friday, August 05, 2022 in Gantar Village, Gantar District, Indramayu Regency. Maintaining physical health is very important for humans, especially during this COVID-19 pandemic. By doing morning exercise activities, it can provide good benefits for the human body and is one way for us to keep our immune system strong and avoid various viruses including the covid- 19 virus. As has been done by the people in Gantar Village who take part in morning exercises and feel better after doing morning exercises.